Recognize the epidemiological and geospatial profile of the Mobile Emergency Care Service: a strategy to optimize response time - Santos, Inácia Jordana de Oliveira; Milani, Renata Delgado; Silva Júnior, José Antonio da; Sousa Sobrinho, Antônio Gomes de; Peixoto, Filipe da Silva; Nascimento, Ellany Gurgel Cosme do (Revista Cubana de Información en Ciencias de la Salud, 2024)
Epidemiological, cross-sectional, descriptive, retrospective study of a quantitative nature, to trace the epidemiological and geospatial profile of the occurrences assisted by the Mobile Emergency Care Service. For that purpose, secondary data from the documents of the Mobile Emergency Care Service of a city in the interior of Rio Grande do Norte were used, considering the frequency of the variables: sex, age group, nature of occurrences, days of the week, ambulance sent, removal inter-hospital care and patient destination. Of the 363 occurrences, most were due to clinical causes, followed by traumatic, psychiatric, and gynecological/obstetric causes, with an emphasis on cardiovascular diseases and transport accidents. aged 19 to 59 years and over 60 years, with the Basic Support Unit providing the majority of care. Among the calls for clinical causes, women stood out, while for traumatic and psychiatric causes, men. The information contributes to the organization and planning of the service and the understanding of the morbidity profile. The geographic distribution highlights the need for integration between health agencies, for the institution of preventive actions, and the redirection of human and financial resources.